Investigation of Sensor for Measurement of Rotation Angle of Sensitive Element in Rotational Paper Pulp Consistometer - Yevhen Pistun; Bohdan Kril; Oleksandr Romaniuk; Oleksandr Kril (Energy Engineering and Control Systems)
This paper presents the results of theoretical and experimental testing of an optical rotation angle sensor of rotational paper pulp consistency meter. It is suggested that a specialized device consisting of two discs with the diameter as large as possible should be applied in the rotational consistency meters. There are holes in the disks. One more optocoupler should be applied for registering the beginning of the signal processing of separate measurements in order to reduce the root-mean square error. The measurement cycle of the sensitive element rotation angle is conducted within a predetermined number of full turns of the main shaft. The research results can be applied during development of the paper pulp rotation consistency meters based on the compensation of the viscous friction torque and based on the direct measurement of the viscous friction by defining the rotation angle of the sensitive element.